Analisa Pengaruh Jumlah Produksi, Harga, dan Investasi Terhadap Volume Ekspor Tembaga Indonesia Tahun 1995-2010 - Sugiarsana, Made; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2012)
In the era of free trade in international trade, competition will be intense. For each country was trying to improve its flagship production of export goods. The problem of this study is how the amount of production, prices, exports and investment towards copper Indonesia in 1995-2010. The analysis technique used is regeresi linear regression. The results of data analysis showed that the amount of production, prices and investment simultaneously significant effect on copper export volume of Indonesia in 1995-2010. Partially only variables that have a significant amount of production while the price variable and the investment does not significantly influence the volume of copper exports in Indonesia in 1995-2010.
Keywords: Copper Exports; Prices; Investment; Production